Adrift in a Boat - Kingston, William Henry Giles, 1814-1880 (Salt Lake City, UT : Project Gutenberg, 2007)
"Adrift in a Boat" by W.H.G. Kingston is a novel written in the mid-19th century. The story follows two young boys, Harry Merryweather and David Moreton, who embark on a picnic adventure that quickly turns perilous after they get trapped by the tide and find themselves adrift on the open sea. As the plot unfolds, they encounter numerous trials, including a shipwreck, a fierce storm, and the challenge of survival while battling anxiety and uncertainty. At the start of the narrative, a cheerful picnic invites families to a beautiful Cornish beach, where the boys initially enjoy their time until their exploration leads to unexpected danger. As the tide rises, they struggle to find safety and are ultimately swept into a series of dramatic events, including the loss of a companion, the eerie presence of a privateer, and the threat of drowning. The opening chapters establish a gripping scenario of survival against the odds, leaving readers eager to discover how Harry and David navigate their dire circumstances and whether they will find their way home. (This is an automatically generated summary.)
Release date is 2007-10-17
Produced by Nick Hodson of London, England
Keywords: Sea stories; Conduct of life -- Juvenile fiction; Shipwreck survival -- Juvenile fiction; Friendship -- Juvenile fiction; Pirates -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Rescues -- Juvenile fiction; Survival skills -- Juvenile fiction